1993
DOI: 10.1111/j.1532-5415.1993.tb06759.x
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Colonization in Residents of Long‐Term Care Facilities: Prevalence and Risk Factors

Abstract: The use of antibiotics, particularly cephalosporins and TMP/SMX, is a significant risk factor for asymptomatic carriage of C. difficile in long-term care facilities. The use of H-2 blockers was also a significant risk factor for carriage; however, this finding has not been reported previously and should be confirmed by independent studies. These medications should be used judiciously in the LTCF population. When diarrheal diseases are encountered in LTCF residents, a high index of suspicion for C. difficile in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 25 publications
3
53
0
3
Order By: Relevance
“…4,10,11 None of these studies controlled for differences in antibiotic use, nor did they distinguish between different types of acid suppressive therapies. One study found a nonsignificant association between acid antisecretory therapy and C. difficile diarrhea, 4 but the lack of statistical significance may have reflected limited power.…”
Section: Discussionmentioning
confidence: 99%
“…4,10,11 None of these studies controlled for differences in antibiotic use, nor did they distinguish between different types of acid suppressive therapies. One study found a nonsignificant association between acid antisecretory therapy and C. difficile diarrhea, 4 but the lack of statistical significance may have reflected limited power.…”
Section: Discussionmentioning
confidence: 99%
“…Much higher rates of colonization, 10 to 50%, are seen in high-risk populations, such as hospitalized patients and long-term-care facility residents. Previous antimicrobial use and previous C. difficile infection (CDI) are predictors of colonization in these populations (68)(69)(70). C. difficile is acquired through the ingestion of spores via the fecal-oral route or through exposure to spores in the environment.…”
Section: Clostridium Difficilementioning
confidence: 99%
“…In addition, many hospitalized patients and long-term care facility (LTCF) residents are asymptomatic carriers of toxigenic C. difficile (1)(2)(3)(4)(5)(6)(7)(8)(9). Although infection control efforts typically focus on patients with C. difficile infection (CDI), there is some evidence that asymptomatic carriers might play an underappreciated role in the transmission of C. difficile.…”
mentioning
confidence: 99%